2014
DOI: 10.1007/s12311-014-0569-0
|View full text |Cite
|
Sign up to set email alerts
|

Normal Motor Adaptation in Cervical Dystonia: A Fundamental Cerebellar Computation is Intact

Abstract: The potential role of the cerebellum in the pathophysiology of dystonia has become a focus of recent research. However, direct evidence for a cerebellar contribution in humans with dystonia is difficult to obtain. We examined motor adaptation, a test of cerebellar function, in 20 subjects with primary cervical dystonia and an equal number of aged matched controls. Adaptation to both visuomotor (distorting visual feedback by 30°) and forcefield (applying a velocity-dependent force) conditions were tested. Our h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 50 publications
6
14
0
1
Order By: Relevance
“…As opposed to healthy individuals, patients did not display modulations of PAS. Similar findings were observed in a separate study in cervical dystonia that used anodal TDCS CB and showed no impact on subsequent PAS applied to M1 [56]. These two studies suggest that loss of cerebellar control over sensorimotor plasticity could underlie alterations of specific motor programs involved in writing.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…As opposed to healthy individuals, patients did not display modulations of PAS. Similar findings were observed in a separate study in cervical dystonia that used anodal TDCS CB and showed no impact on subsequent PAS applied to M1 [56]. These two studies suggest that loss of cerebellar control over sensorimotor plasticity could underlie alterations of specific motor programs involved in writing.…”
Section: Introductionsupporting
confidence: 82%
“…post) ↔ (HC) Koch et al (2014) [57]CDISI: 1, 2, 3, 4 and 5 msCS: 80 % AMTTS: 1 mVKishore et al (2014) [51]PD with LIDsISI: 2.5 msCS: 70 % RMTTS: 1 mViTBSBonnì et al (2014) [58]PCSISI: 1, 2, 3, 4 and 5 msCS: 80 % AMTTS: 1 mVBrusa et al (2014) [59]PSPISI: 1, 2, 3, 4 and 5 msCS: 80 % AMTTS: 1 mVLICIcTBSKoch et al (2009) [48]PD with LIDISI: 100 and 150 msCS: 120 % RMTTS: 1 mV↑ 100 msHubsch et al (2013) [49]WDSI: 100 msCS: 120 % RMTTS: 130 % RMT (adj. post) ↔ (HC) Kishore et al (2014) [51]PD with LIDsISI: 100 msCS: 110 % RMTTS: 1 mVCSPAnodal TDCSSadnicka et al (2014) [56]WD20 % maximal force APBTS: 120 % RMTcTBSKoch et al (2014) [57]CD50 % maximal forceTS: 130 % RMT4. Intracortical facilitationcTBSKoch et al (2009) [48]PDISI: 7, 10 and 15 msCS: 80 % AMTTS: 1 mVCarrillo et al (2013) [36]PDISI: 7, 10 and 15 msCS: 80 % AMTTS: 1 mV ↔ (HC) Di Lorenzo et al (2013) [40]ADISI: 7, 10 and 15 msCS: 80 % AMTTS: 1 mV ↔ (HC) Hubsch et al (2013) [49]WDSI: 15 msCS: 70 % RMTTS: 130 % RMT (adj.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…For example, it has been recently reported that CD patients did not differ from HS in the adaptation of the walking parameter, including speed, step width, step length symmetry and swing/stance ratio (Hoffland et al, 2014). Using a visuomotor task, Sadnicka et al (2014) tested the hypothesis that cerebellar abnormalities in CD patients would translate into motor adaptation deficits. However, not only were adaptation rates (learning) in CD patients found to be similar to those of HS, but the ability to adapt had no relationship with the clinical features of CD.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal motor learning in cervical dystonia was previously shown in a computer-based upper limb target task [24] and in eyeblink conditioning [25] suggesting that cerebellar function is certainly impaired. However, the results of the Hoffland study and recent work by Sadnicka et al [26] should temper these assumptions. Sadnicka et al investigated the adaptation in patients with cervical dystonia to both visuomotor (distorting visual feedback) and force field (applying a velocity-dependent force) perturbations of arm movements using a robotic manipulandum.…”
mentioning
confidence: 83%